Ruth and Esther - Larkin, Katrina J.A. (Sheffield, UK Sheffield Academic, 1996)
Includes bibliographic references and indexes.
Keywords: Bible. O.T. Ruth -- criticism, interpretation, etc; Bible. O.T. Esther -- criticism, interpretation, etc